2023
DOI: 10.1128/spectrum.01496-22
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Tellurium-Based AS101 Compound against Neisseria gonorrhoeae Infectivity

Abstract: Neisseria gonorrhoeae is an obligate human pathogen responsible for gonorrhea, one of the most common sexually transmitted infections. The yearly increased multidrug resistance in GC has led to treatment failure clinically, suggesting an urgent need for novel therapy to combat the global health issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Our previous work has evaluated the effects of a tellurium-based inorganic compound (AS101) on GC [ 37 ]. Comparing teleost-derived AMP to AS101, we found that the teleost-derived AMP possess more bactericidal properties than AS101, as shown in the time-kill curve and TEM, thus suggesting that less antibiotic resistance could occur using AMP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work has evaluated the effects of a tellurium-based inorganic compound (AS101) on GC [ 37 ]. Comparing teleost-derived AMP to AS101, we found that the teleost-derived AMP possess more bactericidal properties than AS101, as shown in the time-kill curve and TEM, thus suggesting that less antibiotic resistance could occur using AMP.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has evaluated the effects of a tellurium-based inorganic compound (AS101) on GC [37].…”
Section: Discussionmentioning
confidence: 99%